Pengaruh Store Environment Terhadap Purchase Intention melalui Store Image Pada D'Kampoeng - Ketut Ratnasari (Jurnal Strategi Pemasaran, 2015)
In-paced life of today's modern, meeting the needs of the Community are more likely on the perceived practical and instant. So is the fulfillment aspects of food and beverages. This can be an opportunity for businesses in the food and beverage sector to sell their products. The purpose of this study alone is to determine and analyze the effect of store environment to purchase itention through store image at D'Kampoeng. This study uses kuantitaf approach with the research method used was a survey. While the population and the sample used in this study are consumers of D'kampoeng. The sampling technique used was accidental sampling. The number of samples used is 68.06 which is then rounded up to 68 people. However, that this study may represent consumers who come in D'Kampoeng the number of respondents that will be used by 100 respondents around 3 months. The result of this analyses is that store environment influence purchase intention through store image at D’Kampung and the management must be more protective about their service quality.